2018
DOI: 10.1371/journal.pone.0197390
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of strains of Neisseria meningitidis causing meningococcal meningitis in Mozambique, 2014: Implications for vaccination against meningococcal meningitis

Abstract: IntroductionIn sub Saharan Africa, the epidemiology, including the distribution of serogroups of strains of N. meningitidis is poorly investigated in countries outside “the meningitis belt”. This study was conducted with the aim to determine the distribution of serogroups of strains of N. meningitidis causing meningococcal meningitis in children and adults in Mozambique.MethodsA total of 106 PCR confirmed Neisseria meningitidis Cerebrospinal Fluid (CSF) samples or isolates were obtained from the biobank of acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The nurse should educate the parents on ensuring that the children are vaccinated against neisseria meningitides. All contacts should be educated about the signs and symptoms of the infection and when to return to the emergency room (Munguambe, 2018) The nurse should be explained the procedure and its risks to the patient and informed consent obtained if relevant in the practice setting. The description should include how the procedure will be performed, why it is being performed, what complications may occur, and how these can be treated.…”
Section: Introductionmentioning
confidence: 99%
“…The nurse should educate the parents on ensuring that the children are vaccinated against neisseria meningitides. All contacts should be educated about the signs and symptoms of the infection and when to return to the emergency room (Munguambe, 2018) The nurse should be explained the procedure and its risks to the patient and informed consent obtained if relevant in the practice setting. The description should include how the procedure will be performed, why it is being performed, what complications may occur, and how these can be treated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results found that age of patient had significant prognostic effect and relation to complications of meningitis with p-value less than 0,05 in both of 2015 and 2016 as its illustrated in the figure (2). Seasonally, figure (3) Moreover, we found that males were highly affected by meningitis over all seasons of 2015 except the summer (figure 4), also, high meningitis infects patient aged between (20-44 years old) during all seasons of the same year except winter (figure 5). However, these seasonal interactions of meningitis infection with age and sex are non-significant statistically during the year 2015.…”
Section: Resultsmentioning
confidence: 67%
“…The phenotypic classification of meningococci, based on structural differences in capsular polysaccharide, lipooligosaccharide (LOS) and outer membrane proteins, is now complemented by genome sequence typing (ST). Meningococcal meningitis is often serious and potentially fatal and death occurs on average in 10% of untreated patients (3). According to the World Health Organization (WHO), an estimated 500,000 cases and 50,000 deaths are attributed to N. meningitidis each year worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Biobanking is becoming increasingly recognised and utilised in Africa in a variety of fields including stroke [7], oncology [8], infectious disease [9] and pregnancy. This summary represents a practical account of the necessary stages required in setting up a large multi-country biorepository and database in low income settings.…”
Section: Discussionmentioning
confidence: 99%